Exploring biomolecular analysis of angiopoietin-like 4 upregulation through lifestyle for atheroprotection and plaque stabilization - Bima Diokta Alparisi; Samira Amanda; Nindy Putri Amalia; Hery Diansyah Putra; Haryadi; Muhammad Ihsan (Published by Universitas Gadjah Mada, 2026)
Atherosclerosis is a chronic inflammatory disease characterized by endothelial dysfunction, lipid metabolic imbalance, and immune activation, ultimately leading to plaque formation and instability. Angiopoietin-like protein 4 (ANGPTL4) has emerged as a key regulator linking lipid metabolism, endothelial function, and inflammatory responses. However, its mechanistic role in atherosclerosis and its modulation by lifestyle factors remain incompletely understood. This review synthesizes 13 original studies comprising preclinical studies, human observational studies, and non-randomized interventions. The analysis focused on the biomolecular role of ANGPTL4 across different stages of atherosclerosis and its regulation by lifestyle factors such as fasting and physical activity. Experimental studies demonstrated that ANGPTL4 exerts a protective role against atherosclerosis by preserving endothelial integrity through Krüppel-like factor–dependent signaling and suppression of endothelial-to-mesenchymal transition. ANGPTL4 also regulates lipid metabolism and constrains macrophage inflammatory activation, thereby limiting plaque progression and instability. In human studies, ANGPTL4 loss-of-function variants were associated with favorable lipid profiles and reduced cardiometabolic risk, whereas elevated circulating levels of ANGPTL family members correlated with atherosclerosis severity and adverse cardiovascular outcomes. Lifestyle-related exposures, including fasting and physical activity, consistently induced ANGPTL4 expression across metabolic tissues. These findings indicate that ANGPTL4 serves as a molecular interface between lipid metabolism, vascular homeostasis, inflammation, and lifestyle-induced metabolic adaptation. The tissue-specific and context-dependent regulation of ANGPTL4 highlights the complexity of its role in atherosclerosis and suggests that therapeutic modulation requires careful consideration of systemic versus local vascular effects. In conclusion, ANGPTL4 is a pivotal mediator in atherosclerosis pathogenesis and metabolic responses to lifestyle factors. Integrating lifestyle-based interventions with therapeutic strategies targeting ANGPTL4 may offer a comprehensive approach for the prevention and management of atherosclerotic cardiovascular disease.